2020
DOI: 10.1101/2020.09.03.20187815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autoimmune and Inflammatory Mechanisms in Cervical Dystonia

Abstract: There are many causes for cervical dystonia (CD), although most cases are idiopathic and a cause cannot be identified. The observation that 10-15% of cases have an affected family member has pointed to genetic causes, but known genes account for only a small fraction of all cases. The current manuscript describes a series of studies focusing on potential autoimmune or inflammatory mechanisms in CD. First, a case-control survey for 32 autoimmune diseases in 271 subjects with CD confirmed prior anecdotal obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…While a more recent population-based study of cervical dystonia found higher rates of cervical spondylosis, soft-tissue disorders, back pain, essential tremor, neck tension, dental caries, and abdominal and pelvic pain, compared to a control cohort [ 12 ]. Autoimmune disorders, such as thyroid disease [ 13 ], myasthenia gravis [ 14 ], and Sjogren’s syndrome [ 15 ], have also been reported at higher rates, with preliminary mixed immunoassays potentially indicating common autoimmune mechanisms in dystonia [ 16 ]. Respiratory symptoms have been attributed to dystonic spasms affecting the respiratory muscles, with evidence of upper airway or diaphragmatic dysfunction [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…While a more recent population-based study of cervical dystonia found higher rates of cervical spondylosis, soft-tissue disorders, back pain, essential tremor, neck tension, dental caries, and abdominal and pelvic pain, compared to a control cohort [ 12 ]. Autoimmune disorders, such as thyroid disease [ 13 ], myasthenia gravis [ 14 ], and Sjogren’s syndrome [ 15 ], have also been reported at higher rates, with preliminary mixed immunoassays potentially indicating common autoimmune mechanisms in dystonia [ 16 ]. Respiratory symptoms have been attributed to dystonic spasms affecting the respiratory muscles, with evidence of upper airway or diaphragmatic dysfunction [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%